Energy consumption optimization of tramway operation based on improved PSO algorithm - Xing, Zongyi; Zhu, Junlin; Zhang, Zhenyu; Qin, Yong; Jia, Limin (Energy (Oxford), 2022)
Tramway has the advantages of reliable operation, energy-saving, and environmental protection, which is an important way to alleviate traffic pressure. Energy consumption optimization of tramway operation is significant in reducing the operation cost. Therefore, the energy consumption optimization model of tramway operation based on the improved PSO algorithm is developed. Firstly, the energy consumption model of the tramway is established based on the energy-saving operation strategy. Then, the competition mechanism-based particle swarm optimization (CM-PSO) algorithm is developed to improve energy-saving performance. Finally, the Guangzhou Haizhu tramway is taken as an example to illustrate the effectiveness of the developed method. The results show that the developed model effectively reduces the tramway operation energy consumption and performs better than the previous methods. •The energy-saving effect of the CM-PSO algorithm is better than other methods.•The operation strategy reduces energy consumption under operation time constraints.•The turning points between different work conditions are found.